How do childhood abuse and neglect affect prosocial behavior? The mediating roles of different empathic components - Chen, Peiyi; Zhang, Qiaofen; Sun, Xiyuan; Ye, Xiaoyang; Wang, You; Yang, Xueling (Frontiers in Psychology, 2023)
Background: Childhood abuse and neglect are typically considered as two different forms of maltreatment. Previous international studies have found differential effects of abuse and neglect on prosocial behavior, but this and the mediating pathway underlying these associations have not been examined in a Chinese sample. Our study aims to examine the effects of childhood abuse and neglect on prosocial behavior in Chinese participants and test the unique mediating roles of different empathic components in these associations. Methods: A total of 1569 young adults (average age = 18.17 years) were recruited from a college that enrolls students from all provinces of China. Participants completed a series of questionnaires, including the Childhood Trauma Questionnaire, Interpersonal Reactivity Index, and Prosocial Tendencies Measure. Path analyses were conducted to determine the mediational relationships. Results: Emotional neglect had significant direct effect on prosocial behavior (β = -0.108, p < 0.001), and could also impact prosocial behavior through the mediating roles of perspective-taking and empathic concern (effect size = -0.091 and -0.097 respectively, p < 0.001). Emotional abuse affected prosocial behavior only through personal distress (effect size = -0.072, p < 0.001). Physical abuse, sexual abuse and physical neglect have little effect on prosocial behavior and empathy. Conclusions: Childhood abuse and neglect have distinct influence on prosocial behavior. Emotional abuse and emotional neglect affect prosocial behavior through distinct pathways. This conclusion could help to establish precise interventions for improving prosocial behavior in maltreated individuals.